Black widow optimization of dead times in asymmetrical 5-level Cascaded H-Bridge Inverters - Ala, G.; Colak, I.; Di Tommaso, A.O.; Miceli, R.; Nevoloso, C.; Scaglione, G.; Schettino, G.; Galluzzo, F. Ricco; Viola, F. (2024 12th International Conference on Smart Grid (icSmartGrid), 2024)
In order to improve the harmonic reduction in a multilevel inverter a new a symmetrical structure with different voltage levels is presented and driven with an innovative control strategy. The asymmetrical structures are able to create a 7-level staircase with a 5 level CHBMLI, levels that can be easily created with renewable sources, the control strategy is able to use the dead times, needed to avoid short circuits in the same legs, in order to decrease the total harmonic distortions. An innovative genetic algorithm, black widow optimization is used. Through simulation, in the Matlab environment, the main benefits and drawbacks of the proposed approach are discussed